Pembiasaan Aktivitas Keagamaan Dalam Penguatan Pendidikan Karakter Profil Pelajar Pancasila Dimensi Beriman dan Bertakwa - Rofifah, Rona Nabilatur; Supriyadi, Supriyadi (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
The formation of a faithful and pious character is a fundamental aspect in the world of education that plays an important role in the formation of personality, strengthening moral and ethical foundations. This study focuses on the implementation of character education based on the Pancasila Student Profile through the approach of habituating religious activities in schools. This study aims to describe habituation based on religious activities in the character education of the Pancasila Student Profile in the dimension of faith and piety to God Almighty. This type of research uses case study research. Data were collected through in-depth interviews with the principal and teachers and using non-participant observation techniques in the habituation of religious activities and documentation in the form of activity schedules, evaluation reports, and photos of activities. The subjects of this study were seven people, namely the principal and class teachers of phase A. The data analysis technique used the Miles and Huberman interactive analysis model. The validity test of the data used in this study used triangulation of sources and techniques. The research findings show that habituation based on religious activities in the implementation of Pancasila Student Profile character education at SD Plus Fatimah Az-Zahro in the dimension of faith and devotion to God Almighty is carried out through five habituation approaches, namely reading the Qur'an, praying Dhuha in congregation, praying Zuhur in congregation, praying, and being fond of giving alms. The habituation approach based on religious activities in schools can strengthen the implementation of Pancasila Student Profile character education, especially in the dimension of faith and piety.